Towards implementing mapping and assessment of ecosystems and their services in Cyprus: A first set of indicators for ecosystem management - Vogiatzakis, Ioannis N.; Zotos, Savvas; Litskas, Vassilis D.; Manolaki, Paraskevi; Sarris, Dimitrios; Stavrinides, Menelaos (My University, 2020)
Ecosystems deliver a range of services that are important for human well-being. Although Ecosystem Services (ES) assessments have been carried out worldwide in different geographical areas, islands are still under-represented. This research presents the first set of indicators developed for Mapping and Assessment of Ecosystems and their Services (MAES) provided by the ecosystems of Cyprus, as required by the EU Biodiversity Strategy, along with the rationale behind the selection criteria. In total, 269 potential indicators were assessed in terms of data availability at the national/subnational level and their suitability for MAES and were classified using a "traffic light" system on the basis of overall suitability (i.e. conceptually and in terms of datasets). The results showed that 89 indicators (Green indicators) can be directly used for assessing ES in Cyprus. Amongst these 89 Green indicators, 28 are considered to be new additions to the EU MAES list, since they were proposed solely for Cyprus ecosystems, as a result of consultation with local stakeholders. Provisioning and cultural services could be adequately mapped, but lack of data was observed for several regulating services (e.g. erosion, pollution, carbon sequestration). Not all Green indicators, identified herein, are relevant for assessing ES provided by ecosystems in Cyprus, whereas Green indicators which measure similar ES might be redundant. For a given geographical context, there might be relevant (and important) indicators which are not included in the MAES list and this is why consultation with stakeholders is advisable. Knowledge gaps and needs for further improving MAES on the island are also discussed.
Keywords: Decision-making; Ecosystem services; Mediterranean islands; Planning; Policy; Sustainability